Elements diffus pour frontieres absorbantes locales en espace-temps - Modaressi, Hormoz; Aubert, Philippe (European Journal of Computational Mechanics, 1998)
In this paper, spectral impedance for absorbing boundaries using second-order paraxial approximation is presented for a linear elastic isotropic media. High-order derivatives then appear which yields to employ the diffuse element method for discretir.e the disp lacement field in the weak jom1.